(untitled) (Revista Contexto & Educação, 2025)
The Ministry of Health defines a person with a disability (PWD) as an individual with a long-term impairment of a physical, mental, intellectual, or sensory nature, whose interaction with one or more barriers may hinder their social participation (Brazil, 2015). Thus, regarding the access of PWD to the healthcare system, particularly in Primary Care, more than just physical adaptations are necessary. Therefore, this study aims to discuss the care of PWD in light of Transcultural Care, based on a reflective study using the Theory Analysis Model proposed by Meleis (2012). Nursing, as a profession and a science, has its essence grounded in human care, requiring a holistic perspective not only on the individual but also on their family and the community environment in which they are inserted (Gomes; Robaína; Budó, 2012). Among the profession’s care models, Madeleine Leininger’s Transcultural Nursing Care Theory (1978) stands out. This theory proposes the development of a set of scientific and humanized knowledge as a tool for universal and culturally specific care practices. It evaluates the patient’s values, beliefs, and behavioral patterns, relating them to their health-disease process. Monticelli (2010) highlights that transcultural care should involve professional activities that preserve, negotiate, or restructure healthcare practices, aligning them with the individual’s customs. Thus, in the context of caring for PWD in light of this theory, nurses must understand health practices related to the individual and the particularities of their condition, acting as mediators in the construction of care. This implies understanding and respecting their way of life to provide humanized care, an effective and individualized care plan, while valuing their autonomy and safety.